(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
This article provides a detailed analysis of the linguistic characteristics of enantiosemy in the Korean language. Enantiosemy is a phenomenon in which a single word or phrase is used with opposite meanings. While this phenomenon exists in various languages, it exhibits unique semantic and pragmatic characteristics in each. The paper examines the concept of enantiosemy in Korean linguistics, its linguistic status, and examples at both grammatical and lexical levels. The study explores the causes of enantiosemy, its pragmatic functions, and its impact on communication. The findings contribute to the understanding of both the general and specific aspects of enantiosemy in the Korean language and lay the foundation for further research on this important linguistic issue.